Kepemimpinan Kepala Sekolah Sebagai Administrator DiSD Negeri Yosodipuro Kecamatan Banjarsari Kota Surakarta. Tesis. AdministrasiPendidikan. Sekolah Pascasarjana. Universitas Muhammadiyah Surakarta. 2015. - Suprihatin, Suprihatin; , Prof. Dr. Hj. Markhamah, M.Hum; , Dr. Hj. Suyatmini (2016)
This study aims to describe the: 1) the leadership of the principal as an administrator within the thoroughness of the data administration learning in SD Negeri Yosodipuro sub-district of Banjarsari Surakarta. 2) Principal Leadership as an administrator in the guidance and counselling in SD Negeri Yosodipuro sub-district of Banjarsari Surakarta. 3) Principal Leadership as an administrator in the administration of the learners in SD Negeri Yosodipuro sub-district of Banjarsari Surakarta. 4) Principal Leadership as an administrator in administration means pasarana in SD Negeri Yosodipuro sub-district of Banjarsari Surakarta. This research uses qualitative research types, design research method using descriptive qualitative. The implementation of this research is the in SD Negeri Yosodipuro sub-district of Banjarsari Surakarta. The time of the research was carried out over six months, from November 2006 until February 2015. The data used in this research is the primary data and secondary data. Source data obtained through interviews and documentation. As a speaker in this research is a teacher and principal of the SD Negeri Yosodipuro. The validity of the data used in this research is the triangulation triangulation methods and sources. Data analysis techniques using interactive analysis (model intertwined) consisting of three components namely data reduction, data and cereal drawdown conclusion. Based on the results of data analysis and discussion of the obtained conclusions that: 1) the leadership of the principal as an administrator within the thoroughness of the data administration learning in SD Negeri Yosodipuro subdistrict of Banjarsari Surakarta are already well underway, where in this case the principal is already assigning to each teacher to make learning device that consists of an annual program, program semester, the calculation of the effective week, development of syllabus and assessment system, learning implementation plan (RPP), as well as enrichment programs and remidial. 2) Principal Leadership as an administrator in the guidance and counselling is currently done by the teacher of the class, but if the problem is felt heavy, then consulted with religious teachers and principals, so for administrators in the guidance and counselling has not been exercised by the principal because it has not been added. 3) Principal Leadership as an administrator in the administration of the students already well underway, in which the principal is already carrying out the administration of the student, including completeness of student data, from the starting stage of admission, administration groups of study, administration of the mutation of stem students book, student, list of present students and student ratings. 4) The leadership of the principal as an administrator in the administration of the infrastructure has not been going well, where the Administration to take note of the facilities and infrastructure of non inventory has not yet been made.